Power Flow Analysis of Weakly Meshed Distribution Network Including DG - Al-Sakkaf, A.; AlMuhaini, M. (Engineering, Technology & Applied Science Research, 2018)
Power flow is one of the essential studies in power system operation and planning. All steady-state parameters for power distribution systems, such as bus voltage magnitudes, angles, power flows, and power losses, can be calculated by conducting power flow analysis. Distribution system features differ from those of transmission system, rendering conventional load flow algorithms inapplicable. In this paper, three distribution power flow techniques are presented and tested to evaluate their performance when applied to a networked distribution system including distributed generation (DG). These are the distribution load flow (DLF) matrix, the enhanced Newton Raphson (ENR), and the robust decoupled (RD) method. IEEE 33-bus system is adopted for implementing the above methods. Radial and weakly meshed configurations are applied to the tested system with DG inclusion to investigate their influence on the power flow study findings.